Cacao pod based ration supplemented with organic Zn: Growth responce on sheeps - Wisri Puastuti; Dwi Yulistiani; I Wayan Mathius; Fransiscus Giyai; Elis Dihansih (Indonesian Center for Animal Research and Development (ICARD), 2010)
Cacao pod can be used as feed to replace grass. The aims of study was to evaluate the growth response of sheep fed on cacao pod based rations to replace grass and supplemented with organic Zn. Fresh cacao pod was chopped to the size of 1-2 cm. In untreated cacao pod (without ammoniation), chopped cacao pod was dried then milled, while in ammoniated cacao pod, the chopped cacao pod was mixed with urea, 1.5% (w/w) and kept in anaerobic conditions for 7 days. After 7 days it was dried and milled. Both, without ammoniated and ammoniated cacao pod were used for ration formulation. The rations were formulated in iso protein and iso energy (16% CP and 70% TDN). The study used 25 male lambs Sumatera Composite breed at age 7-8 months old with average body weight 18.8 ± 2.86 kg. Experiments were conducted using a randomized block design with number of animal in each group was 5. Five treatment rations evaluated were: R = grass + concentrate (positive control); K = cacao pod + concentrate; KZ = cacao pod + concentrate + organic Zn; KU = cacao pod ammoniated + concentrate; KUZ = cacao pod ammoniated + concentrate + organic Zn. The treatment rations were offered for 10 weeks. The results showed that the consumption of cacao pod based rations was higher (P < 0.05) than the grass-basal ration (75.19 g/kg BW0,75 vs 70.22 g/kg BW0,75). Suplementation of Zn organic to ammoniated or untreated cacao pod resulted in no significant difference in DM, and CP intake. DM, OM, CP digestibility and N retention were relatively similar among the fifth rations from 53.13 to 63.91%, from 54.69 to 66.49%, from 66.0 to 79.28% and from 9.5 to 13.4 g/h respectively. R ration had similar NH3 levels with KU ration (21.57 mM vs 22.94 mM) but higher than the K, KZ and KUZ ration (16.45 mM, 16.62 mM and 13.61 mM). VFA concentration showed no difference among treatments (from 140.32 to 179.76 mM). Sheep fed ration R had similar ADG with K and KZ (92.19 g/h vs 83.13 g/h; 93.44 g/h) but higher than the ration KU and KZ (73.44 g/h and 61.72 g/h). From this study can be concluded that grass-based rations can be replaced by the cacao pod based rations supplemented with organic Zn and resulted in relatively similar ADG of 92.19 g/h vs 93.44 g/h. Key Words: Cacao Pod, Ammoniation, Organic Zn, Sheep